Life cycle assessment of nanofiber production obtained by biomass nanospheres from microalgal - Santini, Jéssica Cristine Viera Machado; Fernandes, Liana da Silva; Rossato, Aline; de Sousa Filho, Walter Paixão; Rodrigues Junior, Luiz Fernando; Schneider, Rosana de Cássia de Souza; Colares, Gustavo; Anschau, Kéllen Francine; Neves, Vinicius Machado; Mortari, Sérgio Roberto; Sagrillo, Michele Rorato (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Microalgae are rapidly being employed in carbon fixation due to their benefits over other crops for energy needs, such as high photosynthetic efficiency, massive biomass production and rapid development. Spirulina maxima is a microalgae whose production is based on cultivation with favorable growing conditions. Within the Life Cycle Analysis, the steps that fed into the Impact 2002 system included assembly and cultivation, production and characterization of nanochitosan, flocculation of biomass with nanochitosan, filtration, drying, production and characterization of the nanosphere, and obtaining the microalgae filter. The production stages were evaluated regarding the environmental impacts that could be caused. To evaluate these processes, Life Cycle Analysis (LCA) was applied using SimaPro software version 8.5 and Ecoinvent 3 database with the “Impact 2002+” impact method from the Swiss Federal Institute of Technology. Characterization and normalization data were considered. The impact categories that stood out the most in relation to the release of particulates into the atmosphere by carrying out the steps are carcinogenic, non-carcinogenic, inorganic breathables, depletion of the ozone layer, organic breathables, global warming, non-renewable energy. Within the category of carcinogens (Kg C2H3Cl eq), there is a total of 1.81 kg C2H3Cl eq of released particulates, for non-carcinogens a total of 3.91 Kg C2H3Cl eq of released particulates, inorganic breathables have a total of 0 0418 kg of particulates released during the stages, for the category of damage and destruction of the ozone layer, expressed there is a total of 1.35 E-6 divided between the stages, the organic breathables totaled 0.00771, for the global warming category expressed in kg CO2 eq we have a total of 24.1 and within the non-renewable energy category we have a total of 352 MJ. As a final result, after evaluating the main categories of risks present during the LCA process, the main category of environmental impact was “Damage to human health”. The result obtained is due to the high consumption of electricity.